Exploratory Review of Factors that Influence Village Financial Management - Umi Kulsum; Rudi Bratamanggala (Riviera Publishing, 2024)
A village is a local unit of territory that plays an important role in the progress of a country. The city government has the right and position to manage its funds and resources, which has a significant impact on financial management at the village level. This study aims to determine and analyze the factors that affect village financial management. This study uses a qualitative descriptive method with data collection techniques through literature review. The results of the study show that internal and external factors affect village financial management. Internal factors include the quality of human resources (HR), transparency and accountability, management capacity, and the level of community participation. External factors include government regulations, policies, economic and social conditions, as well as technology and infrastructure. This study has implications for the factors found in the study are the main components that have the potential to affect the effectiveness of village financial management. A deeper understanding of these factors can help city and village governments design more effective and efficient financial management strategies.